Optimization of Land Use Based on the Source and Sink Landscape of Ecosystem Services: A Case Study of Fengdu County in the Three Gorges Reservoir Area, China - Haozhe Zhang; Qingyuan Yang; Huiming Zhang; Lulu Zhou; Hongji Chen (Land, 2021)
Promoting the preservation and appreciation of ecosystem services is an important value guide for land use optimization. In this research, Fengdu County in the Three Gorges Reservoir Area was selected as the focus of a case study. From the perspective of the source and sink landscape of ecosystem services, a MOP model and FLUS model were used to optimize the areas of various land use types and the spatial configurations of those land use types in the study area in 2035 under a strict ecological constraint (SEC) scenario, a moderate ecological constraint (MEC) scenario, and a relaxed ecological constraint (REC) scenario. We also superimposed and adjusted the results of land use optimization under the three ecological constraint scenarios, and obtained land use regionalization results that integrated multiple scenarios. The results indicated that (1) there were large differences in the areas and spatial distributions of the source and sink landscapes under the three scenarios. Under the SEC scenario, the important source landscapes (ISLs), common source landscapes (CSLs), and sink landscapes (SLs) areas covered 1676.62 km2, 1190.43 km2, and 33.81 km2, respectively. A large area of the CSLs and a small area of the SLs were transformed into ISLs area, and the degree of fragmentation of the landscape was low. Under the MEC scenario, the ISLs, CSLs, and SLs areas covered 1609.22 km2, 1241.60 km2, and 49.74 km2, respectively. The development of the source landscapes and sink landscapes was similar, and the degree of fragmentation was moderate. Under the REC scenario, the ISLs, CSLs, and SLs areas covered 1603.96 km2, 1243.32 km2, and 53.58 km2, respectively. A large area of CSLs was transformed into SLs area, and the degree of fragmentation was high. (2) Fengdu County was divided into seven types of areas: ecological conservation area; agricultural production area; construction optimization area; construction-ecological area; ecological-agricultural area; agricultural-construction area; and integrated development area. The results of this study can provide references for the territorial spatial planning and management of ecological barrier zones.